2005
DOI: 10.1104/pp.105.062174
|View full text |Cite
|
Sign up to set email alerts
|

The roothairless1 Gene of Maize Encodes a Homolog of sec3, Which Is Involved in Polar Exocytosis

Abstract: The roothairless1 (rth1) mutant is impaired in root hair elongation and exhibits other growth abnormalities. Unicellular root hairs elongate via localized tip growth, a process mediated by polar exocytosis of secretory vesicles. We report here the cloning of the rth1 gene that encodes a sec3 homolog. In yeast (Saccharomyces cerevisiae) and mammals, sec3 is a subunit of the exocyst complex, which tethers exocytotic vesicles prior to their fusion. The cloning of the rth1 gene associates the homologs of exocyst s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 37 publications
(51 reference statements)
2
152
0
Order By: Relevance
“…S9A, white arrows). In root hair cells, where active exocytosis is required for polarized growth (33,34), it was found that, upon ES2 treatment, the fluorescence recovery of GFP:EXO70A1 after photobleaching was significantly slower compared with control cells (Fig. 4D).…”
Section: The Expression Of Exo70a1 N Terminus Results In Desensitizatmentioning
confidence: 99%
“…S9A, white arrows). In root hair cells, where active exocytosis is required for polarized growth (33,34), it was found that, upon ES2 treatment, the fluorescence recovery of GFP:EXO70A1 after photobleaching was significantly slower compared with control cells (Fig. 4D).…”
Section: The Expression Of Exo70a1 N Terminus Results In Desensitizatmentioning
confidence: 99%
“…The essential function of the exocyst in tip growth in plants has already been demonstrated by genetic studies, although the exact role of the exocyst has not been elucidated yet. Mutations of SEC3 in maize and EXO70A1 in Arabidopsis lead to impaired root hair elongation (Wen et al, 2005;Synek et al, 2006). Mutations of SEC3, SEC5, SEC6, SEC8, and SEC15a in Arabidopsis dramatically affect both pollen germination and pollen tube elongation (Cole et al, 2005;Hála et al, 2008).…”
Section: Functions Of Exo70 Genes In Tip Growthmentioning
confidence: 99%
“…Immunocytochemical analysis showed that SEC6, SEC8, and EXO70A1(At5g03540) are colocalized in tips of growing pollen tubes, which seems to be similar to the polarized localization to the sites of secretion of the exocyst complex in yeast and animals (Hála et al, 2008). Mutations of both SEC3 in maize (Zea mays) and EXO70A1 in Arabidopsis cause a defect in root hair elongation (Wen and Schnable, 1994;Wen et al, 2005), whereas mutations of SEC3, SEC5, SEC6, SEC8, or SEC15a in Arabidopsis lead to defects in pollen germination and pollen tube growth (Cole et al, 2005;Hála et al, 2008). One of these EXO84 genes in Arabidopsis is involved in secretion processes during cytokinesis (Fendrych et al, 2010).…”
mentioning
confidence: 99%
“…Vesicle fusion is accomplished through the action of SNARE proteins (for review, see Lipka et al, 2007), tethering factors (Rab GTPases; for review, see Zerial and McBride, 2001;Molendijk et al, 2004), and presumably aided by components of the exocyst complex (Segui-Simarro et al, 2004), although, to date, mutants defective in subunits of this complex have only been implicated in polar growth (Cole et al, 2005;Wen et al, 2005;Synek et al, 2006;Lavy et al, 2007). The darkstained vesicles were also found in the vicinity of the Golgi apparatus, and it was concluded that they were Golgi derived.…”
Section: Origin Of Cell Plate-building Vesiclesmentioning
confidence: 99%